Biological nitrogen fixation in farming systems of the tropics - Ayanaba, A.; Dart, P.J. (John Wiley and Sons, 1977)
This book is the proceedings of a symposium held at the International Institute of Tropical Agriculture, Ibadan, Nigeria in Oct. 1975. It is divided into sections on general considerations (3 papers); legumes in farming systems of the tropics (4 papers); ecology and physiology of rhizobia (6 papers); nitrogen fixation in legumes (7 papers); non-legume sources of biological N in nature (6 papers); and measuring N gains and losses in farming systems (4 papers). The following are noted.